Cyberbullying Terhadap Perilaku Penonton Konten Tiktok Gaming ‘’OFFICIAL SIR KEJUU’’ - Nadya Nurfauziyah; Een Irianti; Riza Gusti Rahayu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research examines the impact of cyberbullying on viewer behavior on the TikTok platform, especially on the gaming account